Novel DNA-based in situ hybridization method to detect Desmozoon lepeophtherii in Atlantic salmon tissues - Herrero, A.; Palenzuela, Oswaldo; Rodger, H.; Matthews, C.; Marcos-López, Mar; Bron, James; Dagleish, M. P.; Thompson, K. D. (Journal of Fish Diseases, 2022)
The microsporidian Desmozoon lepeophtherii Freeman and Sommerville, 2009 is con- sidered significant in the pathogenesis of gill disease in Atlantic salmon (Salmo salar Linnaeus, 1758). Due to the difficulty in detecting D. lepeophtherii in tissue sections, infections are normally diagnosed by molecular methods, routine haematoxylin and eosin (H&E) stained gill tissue sections and the use of other histochemical stains and labels to confirm the presence of spores. An in situ hybridization (ISH) protocol spe- cific for D. lepeophtherii was developed using DIG-labelled oligonucleotide probes. Diseased Atlantic salmon gills were analysed by ISH, calcofluor white (CW) and H&E. All methods showed high levels of specificity (100%) in their ability to detect D. lepeophtherii, but the sensitivity was higher with ISH (92%), compared with CW (64%) and the presence of microvesicles on H&E stained sections (52%). High levels of D. lepeophtherii spores were significantly associated (p < .05) with the development of D. lepeophtherii-associated pathology in the gills, with Ct values below 19 and over 100 microsporidia/10 mm2 of gill tissue (from the ISH counts) seemingly necessary for the development of microvesicles. The ISH method has the advantage over other his- tological techniques in that it allows all life stages of the microsporidian to be detected in infected salmon gill tissue sections. The project leading to these results has received funding from the European Union’s Horizon 2020 research and innovation programme (TNA programme, project AE070025) at IATS-CSIC research infrastructure, under grant agreement No 652831 (AQUAEXCEL2020). This output reflects only the author’s view and the European Union cannot be held responsible for any use that may be made of the information contained therein. This work was supported financially by Moredun Research Institute and Vet-Aqua International Peer reviewed